2019
DOI: 10.5433/1679-0359.2019v40n3p1033
|View full text |Cite
|
Sign up to set email alerts
|

Structure and development of root gall induced by Meloidogyne javanica in Glycine max L.

Abstract: Galls formed by root-knot nematodes have been studied in several cultivated species focusing on understanding the intimate relationship between parasite and the host plant. Species of Meloidogyne induce the development of a feeding site in the cortex or vascular cylinder of the host plant and are totally dependent on this site formation to complete their life cycle. Therefore, we focused on anatomical, cytological and histochemical changes during the establishment and development of galls and giant cells induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Such an effect is provided by the extension of hyphae in soil (Prasad et al, 2017). Nematode parasitism results in the disorganization of the central cylinder of plant roots (Wanderley & Santos, 2004;Vitela et al, 2019), thereby limiting the absorption of soil solution. R. clarus increased plant phytomass even in the presence of nematodes, evidence of the benefits that the fungus may provide in the control of M. javanica.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an effect is provided by the extension of hyphae in soil (Prasad et al, 2017). Nematode parasitism results in the disorganization of the central cylinder of plant roots (Wanderley & Santos, 2004;Vitela et al, 2019), thereby limiting the absorption of soil solution. R. clarus increased plant phytomass even in the presence of nematodes, evidence of the benefits that the fungus may provide in the control of M. javanica.…”
Section: Resultsmentioning
confidence: 99%
“…infection (Pinheiro et al, 2019). Females of these sedentary endoparasites establish a complex parasitic relationship with hosts, inducing feeding sites characterized by the presence of multinucleated giant cells (Vitela et al, 2019). Adjacent cells undergo hyperplasia and hypertrophy, resulting in the occurrence of nodosities in roots, a symptom also known as galls (Jones et al, 2013).…”
Section: Researchmentioning
confidence: 99%
“…and Heterodera spp., infect host roots and establish feeding sites within the root tissues (Kyndt et al., 2013). It has been suggested that plant sugars are transported into the feeding sites and are stored as starch for nematodes’ carbohydrate needs (Hofmann et al., 2008; Vilele et al., 2019). Two different mechanisms on sucrose supply to feeding sites of sedentary plant‐parasitic nematodes have been uncovered in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…Gall formation results from the hypertrophy of root cortex cells with the differentiation of vascular cylinder cells into giant cells, but it is not a fundamental factor for the success of rootknot nematodes (Vilela et al 2019). Success occurs when the nematode establishes a well-defined feeding site, the coenocyte, and the gall may appear before the coenocyte (Ferraz and Brown 2016).…”
Section: Discussionmentioning
confidence: 99%